Velocity-Dependent Changes in Electrical Efficiency of the Leg Extensors during Eccentric Isokinetic Muscle Actions - Hill, Ethan C.; Housh, Terry J.; Camic, Clayton L.; Smith, Cory M.; Schmidt, Richard J.; Johnson, Glen (International Journal of Sports Medicine, 2018)
The mechanisms underlying velocity-specific decreases in torque production during eccentric muscle actions remain unclear. Therefore, the purpose of the present study was to examine electrical efficiency at 60 and 180°·s−1 during fatiguing, maximal eccentric isokinetic muscle actions of the leg extensors. Thirteen men visited the lab on two occasions and randomly performed 30 repeated maximal eccentric isokinetic muscle actions of the leg extensors at 60 and 180°·s−¹ through a 90° range of motion. Polynomial regression analyses and separate repeated measures ANOVAs were used to examine the composite patterns of responses for electromyographic amplitude, eccentric torque, and electrical efficiency across the 60 and 180°·s−¹ protocols. Eccentric torque remained unchanged across the 30 maximal eccentric muscle actions performed at 60 and 180°·s−1. Electromyographic amplitude and electrical efficiency, however, increased linearly across the 180°·s−1 protocol, but there were no changes for either electromyographic amplitude or electrical efficiency during the 60°·s−1 fatiguing protocol. These findings indicated that performing eccentric muscle actions at a fast velocity (i. e., 180°·s−1) was characterized by greater efficiency (i. e., decreased electrical efficiency) compared to eccentric muscle actions performed at a slow velocity (i. e., 60°·s−1). Thus, it is possible that eccentric muscle actions performed at fast velocities are more robust to fatigue due, in part, to greater efficiency compared to slow-velocity eccentric muscle actions.
Keywords: muscle fatigue; EMG; isokinetic; motor control